IN VITRO EVALUATION OF HYPOLIPIDEMIC EFFECT OF EXTRACTS OF MEDICINAL DRACAENA CINNABARI BALF. F. RESIN: In vitro evaluation of hypolipidemic effect - YASSER HUSSEIN EISSA MOHAMMED; DEEPIKA HS; FARES HEZAM AL-OSTOOT; ZABIULLA; ANILAKUMAR; SHAUKATH ARA KHANUM (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the study was to in vitro evaluate of hypolipidemic effect of extracts of medicinal Dracaena cinnabari Balf. f. resin. Methods: About 800 g of dry powder of the resin of dracaena cinnabar was taken in a Soxhlet apparatus and subjected for sequential extraction of solvents from non-polar to polar end (hexane, benzene, diethyl ether, dichloromethane, chloroform, ethyl acetate, acetone, ethanol, methanol, and water); the extract samples were kept at 4°C for further assays. All the extracts were subjected to glucose uptake assay. Results: The ethanol extract showed significant (p<0.05) hypolipidemic effect by decreasing the activity of enzyme such as significant reduction in the pancreatic lipase enzyme, malic dehydrogenase enzyme, and glucose-6-phosphate dehydrogenase enzyme with IC50 13, 13, and 14, respectively. This results were similar to the standard drug atorvastatin with IC50 12, 16, and 17, respectively. Ethanol extract exhibited significant atherogenic index and percentage protection against hyperlipidemia. The potential biological activity of ethanol extract may be attributed to the highest polarity which needs further investigation.